Analysing Consumer Adoption Intentions of Drone-enabled Food Delivery Services: The Moderating Role of Uncertainty Avoidance - Shakeel Ahmad; Xue Chaogai; Sayed Kifayat Shah; József Popp; Angel Acevedo-Duque (Amfiteatru Economic)
While drone-enabled food delivery continues to gain prominence, a notable research gap exists in comprehending the impact of real-life psychological challenges — specifically autonomy, competence, and relatedness — on consumer adoption intention in various cultural contexts. This study explores the identified research gap by analysing these challenges through the self-determination theory lens, employing partial least squares structural equation modelling to evaluate survey responses from 423 participants in South Korea and China. The results of our study revealed that the autonomy problem has no significant effect, while the competency problem has a significant positive impact on adoption intentions for drone-enabled food delivery services in both South Korea and China. The effect of relatedness was positive and significant in China, but negative and significant in the South Korean context. These data also demonstrated a moderating impact of cultural dimension (uncertainty avoidance) on a relationship between these factors and adoption intention, demonstrating how culture impacts consumer adoption behaviour. Our results in this research are one of the first to contextualise basic issues by filling gaps in the current literature and offering valuable insights for food service businesses. Our study’s results will also guide the formation of effective drone-enabled food delivery systems in diverse societies by supporting businesses in tailoring their methods to match consumer behaviours.